2019
DOI: 10.1021/acsomega.9b00691
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Compound, Emulsification, and Antibacterial Activity of Modified 1,2,4-Trizaole Derivatives

Abstract: Three modified 1,2,4-trizaole derivatives were synthesized and compounded in pairs. Their structures were confirmed by 1 H NMR and ESI-MS. Antibacterial tests were proceeded to evaluate the fungicidal activity of synthesized compounds. The results of antibacterial tests showed that the synthesized compounds exhibited good antibacterial activities against Coriolus versicolor , Gloeophyllum trabeum , Trichoderma viride, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…18 For the triazole fungicide tebuconazole, nevertheless, the presence of the bulky tert-butyl group makes the asymmetric synthesis of its enantiomers by chemical methods a significant challenge. 19 To our current knowledge, the optical purity of tebuconazole enantiomers can only be obtained via chiral high-performance liquid chromatography (HPLC) resolution 20 (Scheme 2). This chiral HPLC resolution approach, however, has inherent limitations in terms of high cost and low efficiency for industrial production.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 For the triazole fungicide tebuconazole, nevertheless, the presence of the bulky tert-butyl group makes the asymmetric synthesis of its enantiomers by chemical methods a significant challenge. 19 To our current knowledge, the optical purity of tebuconazole enantiomers can only be obtained via chiral high-performance liquid chromatography (HPLC) resolution 20 (Scheme 2). This chiral HPLC resolution approach, however, has inherent limitations in terms of high cost and low efficiency for industrial production.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chang et al reported the chemical synthesis of ( S )-flutriafol (98% ee ) from its epoxy-precursor ( S )-2,2-disubstituted oxirane, which was asymmetric synthesized through the application of a noble metal rhodium­(I)-chiral diene catalyst . For the triazole fungicide tebuconazole, nevertheless, the presence of the bulky tert -butyl group makes the asymmetric synthesis of its enantiomers by chemical methods a significant challenge . To our current knowledge, the optical purity of tebuconazole enantiomers can only be obtained via chiral high-performance liquid chromatography (HPLC) resolution (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Triazoles are five-membered heterocyclic compounds composed of two carbon atoms and three nitrogen atoms. Many nitrogen-rich triazole derivatives can act as weak Lewis bases and are found to be biologically active species. They are considered pharmacophores capable of interacting with specific biological targets, which are widely used as antitumor, antibacterial, antifungal, and prebiotic agents . Several commercial drugs with triazole cores have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%